La noción de sujeto en el último Foucault - González Moreno, Edith (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The topic of the investigation fellow's notion in last Foucault" faces three central matters; the ethical thing, the moral thing and the political thing. In that sense, we could underline even that good part of Michel's investigations Foucault was sustained in the necessity to respond to the following questions; what is it to be subject?, what it dominates the one fellow?, and if the possibility exists of living in freedom. Taking in consideration the above-mentioned this thesis intends to observe the binomials to fellow-be able to and fellow - ethics. Located in the horizon of the philosophy foucaultiana the one central problem settles down genealogies between two; of ourselves in relation to the one field of power to the ontology of ourselves in relation to the field of the ethics.. Of particular way will be considering the question of how the fellow is constituted in that transition that he/she goes of the fellow immerse in the problem from the power to the fellow capable of to be stylized starting from the restlessness of yes. I consider that between to watch over and to punish (1975) and until History of the sexuality II and III (1984) the main axes of continuity and rupture settle down in the speech Foucauldian around the fellow's problem. It is there where the questions around the fellow they acquire the biggest relevance. However, it is pertinent to consider that three roads exist of approach to the proposal of the subjectivity in Michel's philosophy Foucault. The composed by the language and the knowledge, that of the environment of the power and, finally that of the sense ethical whose central proposal is in the diverse forms of care of yes of the fellow Foucauldian. We assume then that fellow's denomination this given in dependence of their approach forms.

El tema de la investigación “La noción de sujeto en el último Foucault” enfrenta tres asuntos centrales; lo ético, lo moral y lo político. En ese sentido, podríamos subrayar incluso que buena parte de las investigaciones de Michel Foucault se sostuvieron en la necesidad de responder a las cuestiones siguientes; ¿qué es ser sujeto?, ¿qué domina al sujeto? y si existe la posibilidad de vivir en libertad. Tomando en consideración lo anterior esta tesis se propone observar los binomios sujeto-poder y sujeto- ética. Ubicada en el horizonte de la filosofía foucaultiana el problema central se establece entre dos genealogías; de nosotros mismos en relación al campo de poder a la ontología de nosotros mismos en relación al campo de la ética. De manera particular estaremos considerando la cuestión de cómo se constituye el sujeto en esa transición que va del sujeto inmerso en la problemática del poder al sujeto capaz de estilizarse a partir de la inquietud de sí. Considero que entre Vigilar y Castigar (1975) y hasta Historia de la sexualidad II y III (1984) se establecen los principales ejes de continuidad y ruptura en el discurso foucaultiano en torno al problema del sujeto. Es ahí donde las preguntas en torno al sujeto adquieren la mayor relevancia. Sin embargo, es pertinente considerar que existen tres vías de aproximación a la propuesta de la subjetividad en la filosofía de Michel Foucault. La compuesta por el lenguaje y el saber, la del ámbito del poder y, finalmente la del sentido ético cuya propuesta central se encuentra en las diversas formas de cuidado de sí del sujeto foucaultiano. Asumimos pues, que la denominación de sujeto está dada en dependencia de sus formas de aproximación.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2009-0026; Michel Foucault; Arte; Sexualidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/56